El cabildo de indígenas: De la opresión colonial a la resistencia contemporánea. el caso del pueblo quillasinga de mocondino (San Juan De Pasto, Colombia) (2023)
The institution of the Council of Indigenous, Colonial origin, Colombia has suffered a series of historical transformations that have become, at present, the main community organization for the defense of the autonomy of indigenous peoples, being, in the case quillasinga's people of Mocondino (San Juan de Pasto), is the element that connects the ancient past to the present and historical reconstruction resistance against the abuses of contemporary legal and political demise by 1948, based on the idea that the past is ahead, marking the path where walk and to retrace must roads of the future. From a Colonial institution of social control and subjugation of native peoples, the council has become the stronghold for community resistance to the abuses in the republic have continued addition of the element dimensions Mocondino's history as a indissoluble and moving, under the current political and legal situations initiated in 1991 with the enactment of Law 21 (Convention 169/1989 of the ILO) and the current Constitution.